2008
DOI: 10.1038/nature06608
|View full text |Cite
|
Sign up to set email alerts
|

SLAC1 is required for plant guard cell S-type anion channel function in stomatal signalling

Abstract: Stomatal pores, formed by two surrounding guard cells in the epidermis of plant leaves, allow influx of atmospheric carbon dioxide in exchange for transpirational water loss. Stomata also restrict the entry of ozone-an important air pollutant that has an increasingly negative impact on crop yields, and thus global carbon fixation 1 and climate change 2 . The aperture of stomatal pores is regulated by the transport of osmotically active ions and metabolites across guard cell membranes 3,4 . Despite the vital ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
879
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 740 publications
(905 citation statements)
references
References 42 publications
22
879
1
3
Order By: Relevance
“…Although several proteins have been shown to function in CO 2 -regulated stomatal response, some critical components are still missing 5,6,18 . Because membrane transporters play an important role in modulating stomatal response to external signals 5,6,[14][15][16][38][39][40] , we hypothesized that mutations in many of such transporters may affect stomatal responses to environmental signals including CO 2 concentration. We identified a large number of genes encoding potential solute transporters and collected T-DNA insertion mutants for these genes to compile a mutant library.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several proteins have been shown to function in CO 2 -regulated stomatal response, some critical components are still missing 5,6,18 . Because membrane transporters play an important role in modulating stomatal response to external signals 5,6,[14][15][16][38][39][40] , we hypothesized that mutations in many of such transporters may affect stomatal responses to environmental signals including CO 2 concentration. We identified a large number of genes encoding potential solute transporters and collected T-DNA insertion mutants for these genes to compile a mutant library.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated CO 2 concentration activates anion channels, resulting in depolarization of plasma membrane in guard cells, causing efflux of solutes and stomatal closure [7][8][9][10] . Earlier studies in Arabidopsis identified several mutants with defects in CO 2 -induced stomatal movements [11][12][13][14][15][16][17][18][19] . However, most of these mutants including abi1-1, abi2-1, gca2, ost1 and slac1 were insensitive to both CO 2 and abscisic acid (ABA), representing components shared by both signalling pathways 5,20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The NtrbohD protein, 28 G protein-coupled receptors (GPCRs), 29 fast vacuolar (FV) channels, K + -selective vacuolar (VK) cation channels, 30 slow vacuolar (SV) channels, slow anion channel-associated 1 (SLAC1) 31,32 and H + -ATPases (AHA1 and AHA2) 33 are localized to the membrane and function during abiotic or biotic responses in guard cells. 34 These findings also demonstrate that the guard cell signal transduction in response to biotic and abiotic signals shares some common steps, including NO accumulation in guard cells.…”
Section: Role Of Vpe In Stomatal Movementmentioning
confidence: 99%
“…Stomata regulate the entry of ozone into the leaf (Vahisalu et al, 2008), and when ozone reaches the apoplast, production of toxic reactive oxygen species (ROS) is initiated (Mahalingam et al, 2006;Wohlgemuth et al, 2002). Symptoms range from accelerated senescence (Karnosky et al, 1996) and a decrease in growth rate (Karnosky et al, 1996Wittig et al, 2009), to foliar injury manifested as necrotic lesions analogous to those formed during the hypersensitive response (HR) .…”
Section: Introductionmentioning
confidence: 99%